Cloning, expression, and characteristic analysis of the novel β‐galactosidase from silkworm, Bombyx mori. Issue 9 (27th August 2021) - Yi, Yongzhu; Li, Jialei; Zong, Zhipeng; Liu, Xingjian; Song, Haozhi; Wang, Haining; Zhang, Zhifang; Zhang, Huan; Li, Yinü
Summary: β‐Galactosidase is a critical exoglycosidase involved in the hydrolysis of lactose, the modification and degradation of glycoprotein in vivo. In this study, the β‐galactosidase gene of silkworm ( BmGal ), whose cDNA comprises 11 exons and contains an intact ORF of 1, 821 bp, was cloned. The protein sequence of BmGal showed high similarity with other known insect β ‐ galactosidases. No activity of the BmGal expressed in Escherichia coli or Pichia pastoris was detected while it was successfully expressed with high enzyme activity in baculovirus expression system in silkworm, and the electrophoresis result revealed that the BmGal showed activity in oligomer mode. Enzyme activity assay showed that its optimum pH was 8.4 and its optimum temperature was 40 °C. What is more, we found that iron ions can stimulate the activity of the enzyme while cobalt, nickel, or lead ions can inhibit its activity significantly. Besides, the temporal–spatial transcription pattern of the BmGal mRNA level was analyzed, which showed that BmGal was transcribed at the highest level in the fifth larval instar but relatively low level in the pupal and adult stage, and the highest transcriptional level of BmGal was found in testis among all the tissues concerned.